Development of a Web Based E-Commerce System for Bouquet Ordering: A Case Study of Maiflorist - Asmainur; Novia Hasdyna; Rahmat (Jurnal Elektronika dan Teknologi Informasi, 2024)
E-commerce has become a widely adopted method for online purchasing, providing convenience and accessibility for both businesses and consumers. A web-based sales information system expands sales reach and enables business operators to efficiently manage and access critical information. This study investigates the development of a website-based e-commerce information system specifically designed for bouquet orders, addressing the need for efficient order management in the floral retail sector. The research employs a descriptive qualitative approach, supported by library research, and utilizes system design tools including UML, activity diagrams, context diagrams, and flowcharts to design and streamline the bouquet ordering process. The system was evaluated through user testing, revealing that the proposed website-based e-commerce platform substantially simplifies the ordering experience for customers. Key features include an admin login page, administrator dashboard, customer registration and login pages, bouquet homepage, bouquet catalog, product information, and shopping cart. This system enables Maiflorist to manage inventory efficiently and supports warehouse, sales, and purchasing staff in organizing product management, leading to faster order processing and enhanced customer satisfaction